2013
DOI: 10.1108/ijm-07-2013-0174
|View full text |Cite
|
Sign up to set email alerts
|

Organizational commitment within a contemporary career context

Abstract: Purpose: This paper analyzes the relation between the underlying dimensions of protean (self direction and values driven) and boundaryless (boundaryless mindset and organizational mobility preference) career attitudes (Briscoe et al., 2006) and organizational commitment, within today's unstable and uncertain business scenario.Design/methodology/approach: Data was collected from 167 professionals attending graduate and post-graduate distance learning courses. The hypotheses were tested using hierarchical regres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
50
3
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 42 publications
(62 citation statements)
references
References 76 publications
7
50
3
2
Order By: Relevance
“…Research has also indicated that individuals engaging in boundaryless careers have distinct career attitudes. For example, they show less organizational commitment (Enache et al, ), and prefer their subjective satisfaction and work‐life balance to elements such as pay and promotion outcomes, as well as high occupational status (Lyons et al, ). Other studies focus on the impact of the psychological contract (the implicit non‐written contract based on the expectations of the worker and employer (Argyris, ; Levinson et al, )) on the career of individuals.…”
Section: Research Propositionsmentioning
confidence: 99%
“…Research has also indicated that individuals engaging in boundaryless careers have distinct career attitudes. For example, they show less organizational commitment (Enache et al, ), and prefer their subjective satisfaction and work‐life balance to elements such as pay and promotion outcomes, as well as high occupational status (Lyons et al, ). Other studies focus on the impact of the psychological contract (the implicit non‐written contract based on the expectations of the worker and employer (Argyris, ; Levinson et al, )) on the career of individuals.…”
Section: Research Propositionsmentioning
confidence: 99%
“…Keempat, pemboleh ubah-pemboleh ubah tidak bersandar lain juga perlu diambil kira dalam kajian akan datang seperti jenis latihan dan kaedah latihan kerana ia sering dilihat sebagai peramal yang penting kepada sikap dan kelakuan individu (Jacobs & Mohammad Jaseem 2012;Pederson et al 2013). Akhir sekali, pemboleh ubah bersandar lain juga perlu diambil kira dalam kajian akan datang seperti kepuasan kerja, prestasi kerja dan komitmen organisasi kerana ia kerap dilihat sebagai akibat yang sangat penting daripada pelaksanaan program pembangunan kepimpinan (Abdul Rahim 2013; Enache et al 2013). Sekiranya cadangan di atas diambil kira ia dapat membantu menghasilkan dapatan kajian yang lebih mantap pada masa akan datang.…”
Section: Perbincangan Dan Implikasiunclassified
“…Additionally, ethical climate can influence organizational commitment [58]. The term "organizational commitment" refers to a force that binds an individual to be involved in organizational activities and to remain in the organization [66,67]. Since employees who perceive a positive ethical climate are committed to their organization, they are expected to be committed to their organization's mission of sustainable development as well.…”
Section: Ethical Climatementioning
confidence: 99%